The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1177/10778012211032706
|View full text |Cite
|
Sign up to set email alerts
|

Violence Against North Korean Refugee Women: Doubly Victimized By Repatriation and Premigration Traumatic Experiences

Abstract: This study investigates the influence of traumatic events on the mental health of North Korean refugee women by examining the prevalence and severity of posttraumatic stress disorder (PTSD), depression, and anxiety in comparison with their male counterparts (women = 496; men = 131). Our results suggest that women are at greater risk of developing mental health problems than men. In particular, symptoms of PTSD and anxiety were higher among women who experienced forced repatriation to North Korea, which is oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…26 The range of CPTSD prevalence was 11.3% 27 to 40.7%, 9 while another study reported a lifetime prevalence of 15.3%. 11 Twenty-four studies were conducted with participants living in the community, 9,11,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][46][47][48]61,62 8 studies at Hanawon (The Settlement Support Center for North Korean defectors), 26,27,[50][51][52][53][54][55] 6 studies at medical centers, 25,45,48,[56][57][58][59] and 2 studies were conducted using an online survey. 49,60 Out of 40 studies reviewed, only one study reported the longitudinal trajectories of the mental health of North Korean defectors.…”
Section: General Characteristics Of the Included Proms And Studiesmentioning
confidence: 99%
“…26 The range of CPTSD prevalence was 11.3% 27 to 40.7%, 9 while another study reported a lifetime prevalence of 15.3%. 11 Twenty-four studies were conducted with participants living in the community, 9,11,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][46][47][48]61,62 8 studies at Hanawon (The Settlement Support Center for North Korean defectors), 26,27,[50][51][52][53][54][55] 6 studies at medical centers, 25,45,48,[56][57][58][59] and 2 studies were conducted using an online survey. 49,60 Out of 40 studies reviewed, only one study reported the longitudinal trajectories of the mental health of North Korean defectors.…”
Section: General Characteristics Of the Included Proms And Studiesmentioning
confidence: 99%